Arterial spin labeling cerebral perfusion magnetic resonance imaging in migraine aura: an observational study - Wolf, Marc; Eisele, Philipp; Roßmanith, Christina; Griebe, Martin; Gass, Achim; Hennerici, Michael G.; Szabo, Kristina; Kern, Rolf (Journal of stroke and cerebrovascular diseases, 2018)
Background - Changes in cerebral perfusion during migraine with aura (MA) have been assessed mainly using dynamic susceptibility contrast (DSC) magnetic resonance perfusion imaging. A contrast agent-free method to assess these changes would be desirable. We assessed changes in cerebral perfusion during MA using arterial spin labeling (ASL) perfusion magnetic resonance imaging. - Methods - We investigated 4 patients with a standardized protocol including ASL perfusion imaging during MA (n = 2) or early headache phase (n = 2) and asymptomatic follow-up. Semiquantitative evaluation was done using a region of interest (ROI) within hypoperfused or hyperperfused areas and corresponding ROIs in the contralateral hemisphere. Relative ratios of mean perfusion in the corresponding ROIs were calculated. DSC imaging was done at initial time points and compared visually with ASL findings. - Results - In all patients, regional perfusion changes were detected in the acute phase. These abnormalities did not respect the boundaries of major cerebral vascular territories but overlapped onto adjoining regions. During MA, adjacent hypoperfused and hyperperfused areas were found, whereas during headache, regional hyperperfusion only was observed. Perfusion abnormalities normalized on follow-up. - Conclusions - ASL perfusion imaging is a contrast agent-free method suitable for assessment of reversible perfusion changes during or immediately after MA.
Gesehen am 30.09.2020